PENGARUH LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN, PROFITABILITAS DAN AGRESIVITAS PAJAK TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN NON KEUANGAN - Suriani Br. Ginting; Anita Tarihoran (Universitas Methodist Indonesia, 2023)
This research aims to determine and analyze the influence of Leverage, Liquidity, Company Size, Profitability and Tax Aggressiveness on Social Responsibility Disclosure in Non-Financial Companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The population in this research is non-financial companies. The sampling method used was the purposive sampling method and a research sample of 130 was obtained. This research used Multiple Linear Regression analysis testing. The results of the analysis show that simultaneously Leverage, Liquidity, Company Size, Profitability and Tax Aggressiveness have a significant effect on Social Responsibility Disclosure. Partially, Liquidity has an effect on Social Responsibility Disclosure, but Leverage, Company Size, Profitability and Tax Aggressiveness have no effect on Social Responsibility Disclosure in non-financial companies listed on the Indonesia Stock Exchange for the 2017-2020 period.